Recent advances in small molecule LpxC inhibitors against gram-negative bacteria (2014–2024) - Ji, Pengpeng; Ma, Meng; Geng, Xiaoyue; Zhang, Jian (Frontiers in Microbiology, 2025)
In 2024, WHO added multiple multidrug-resistant (MDR) Gram-negative bacteria to the bacteria priority pathogens list, and the continued increase in MDR Gram-negative bacteria poses a serious threat to public health. Uridine diphosphate-3-O-(hydroxymyristoyl)-N-acetylglucosamine deacetylase (LpxC) is a metalloenzyme cofactored with zinc ions, which is a key enzyme in the synthesis of outer membrane lipid A in Gram negative bacteria. LpxC is highly conserved and homologous among different Gram-negative bacteria, which makes LpxC a promising target against multidrug-resistant Gram-negative bacteria. Since the first report of the arazoline LpxC inhibitor L-573, 655, a large number of small molecule LpxC inhibitors against Gram-negative bacteria have been synthesized and tested, such as TU-514, CHIR-090, ACHN-975 and TP0586532. However, only ACHN-975 entered clinical phase I trials and was discontinued due to safety concerns, so far none of the LpxC inhibitors are available. This paper mainly focuses on the structure optimization, conformational relationship and animal toxicity of small molecule LpxC inhibitors over the past 10 years, especially in the last 5 years, in order to provide ideas for the development and clinical research of LpxC inhibitors.